Determinants of development of third party liability insurance: Selected approaches, experience and trends in Poland - Maria Gasińska (Foundations of Management, 2016)
The article constitutes an attempt at discussing the determinants of the development of third party liability insurance in historical perspective and on the basis of the observation of trends witnessed in this field nowadays. The identified factors are linked to the functioning of both the demand and the supply aspect of the third party liability insurance market, providing a valuable indicator for insurance practice. The past decade has witnessed steady, though slow, expansion of the third party liability insurance market in terms of the number of contracts concluded, the share of the contributions toward it in the total contribution value as well as the level of the gross contribution assigned. The article characterizes four groups of factors responsible for the third party liability insurance market expansion, namely: (a) determinants resulting from relations between the parties and subjects of the third party liability insurance relation against the complex nature and specific character of the third party liability function; (b) determinants linked to the dynamic development of the so called risk-generating techniques and technologies leading to growth in the development of the so-called damage potential threatening both participants in the production process (including the service provision process) as well as product users and service recipients; (c) determinants of socioeconomic character, in particular the level of legal and insurance awareness of potential damage perpetrators and injured parties as well as material standing of households and financial standing of economic entities; (d) determinants linked to legal regulations, in particular, the leading role of regulations separating the compensatory function of third party liability with respect to the penal function in shaping the scope and value of regulations tightening the scope and principles of third party liability in certain areas of economic turnover and introducing insurance compulsion.
Keywords: G22; 650; risk management of third party liability insurance; third party liability insurance; determinants of the third party liability insurance market